2022
DOI: 10.1126/sciimmunol.abo0226
|View full text |Cite
|
Sign up to set email alerts
|

A modified vaccinia Ankara vaccine expressing spike and nucleocapsid protects rhesus macaques against SARS-CoV-2 Delta infection

Abstract: SARS-CoV-2 vaccines should induce broadly cross-reactive humoral and T cell responses to protect against emerging variants of concern (VOCs). Here, we inactivated the furin-cleavage site (FCS) of spike expressed by a modified vaccinia Ankara (MVA) virus vaccine (MVA/SdFCS) and found that FCS inactivation markedly increased spike binding to human ACE2. Following vaccination of mice, the MVA/SdFCS vaccine induced 8-fold higher neutralizing antibodies compared to MVA/S, which expressed spike without FCS inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…The emergence of SARS-CoV-2 VOCs has posed challenges to the current S-targeting vaccines ( 4 8 ), and next-generation vaccine strategies may benefit from multivalency ( 46 ). Several studies have tested multivalent SARS-CoV-2 candidate vaccines that include the N protein, including adenoviral ( 23 , 47 ) and modified vaccinia Ankara ( 48 , 49 ) vectors. These studies did not compare efficacy with the current, clinically proven S-targeting vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of SARS-CoV-2 VOCs has posed challenges to the current S-targeting vaccines ( 4 8 ), and next-generation vaccine strategies may benefit from multivalency ( 46 ). Several studies have tested multivalent SARS-CoV-2 candidate vaccines that include the N protein, including adenoviral ( 23 , 47 ) and modified vaccinia Ankara ( 48 , 49 ) vectors. These studies did not compare efficacy with the current, clinically proven S-targeting vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A higher magnitude of serum and mucosal IgG, and functional Abdependent cellular activity was observed in the IM-vaccinated RhMs. Nasal anti-RBD IgG and NAbs, as well as serum ADCD, ADCP and ADNKA, were found to inversely correlate with viral load, providing further evidence for the collaborative efforts of neutralising and non-neutralising antibody to protect against SARS-CoV-2 challenge (101). T cell responses were comparable between the IM and buccal administration routes, hence they may contribute to protection also (101).…”
Section: Alternative Vaccine Administration Routesmentioning
confidence: 82%
“…The vaccine has been evaluated in a phase I clinical trial, which has indicated that the vaccine is well tolerated and elicits S-and N-specific immune responses in healthy participants [87]. Similarly, another independent study has investigated the effect of a recombinant MVA vaccine expressing S and N proteins (MVA/SdFCS-N) in NHPs against the SARS-CoV-2 Delta variant [88]. Among the different routes of administration, MVA/ SdFCS-N administration via an intramuscular route has been found to better protection against the Delta variant than other routes [88].…”
Section: Multivalent Sars-cov-2 Vaccines Expressing Multiple Viral Pr...mentioning
confidence: 99%
“…Similarly, another independent study has investigated the effect of a recombinant MVA vaccine expressing S and N proteins (MVA/SdFCS-N) in NHPs against the SARS-CoV-2 Delta variant [88]. Among the different routes of administration, MVA/ SdFCS-N administration via an intramuscular route has been found to better protection against the Delta variant than other routes [88].…”
Section: Multivalent Sars-cov-2 Vaccines Expressing Multiple Viral Pr...mentioning
confidence: 99%